Tangential Essentials II

Geometry Level 5

In the semicircle of radius 1 1 , the point selected on the circumference forms two identical incircles each inscribed in their own triangles, where one of them is an incircle of a right triangle. There exists the unique positive radius, such that the centrally positioned circle, sharing one point of tangency with the circumference of the circle and also one point of tangency with the largest triangle, has the same radius as two incircles.

If the radius is R R , input 1 0 6 R \lfloor 10^6 R\rfloor as your answer.


Try this sister problem first before you attempt this one.


The answer is 243477.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

David Vreken
Mar 17, 2021

Label the diagram as follows:

By symmetry on the top left circle, D F DF is the perpendicular bisector of A C AC , so A E F A C B \triangle AEF \sim \triangle ACB by AA similarity, and since E F = D F D E = 1 2 R EF = DF - DE = 1 - 2R , that makes C B = E F A C A E = ( 1 2 R ) 2 = 2 4 R CB = EF \cdot \cfrac{AC}{AE} = (1 - 2R) \cdot 2 = 2 - 4R .

By the Pythagorean Theorem on A C B \triangle ACB , A C = A B 2 C B 2 = 2 2 + ( 2 4 R ) 2 = 4 R R 2 AC = \sqrt{AB^2 - CB^2} = \sqrt{2^2 + (2 - 4R)^2} = 4\sqrt{R - R^2} .

Let k = G C k = GC . By the Pythagorean Theorem on G C B \triangle GCB , G B = G C 2 + C B 2 = k 2 + ( 2 4 R ) 2 GB = \sqrt{GC^2 + CB^2} = \sqrt{k^2 + (2 - 4R)^2}

Also from right G C B \triangle GCB , R = 1 2 ( G C + C B G B ) = 1 2 ( k + 2 4 R k 2 + ( 2 4 R ) 2 ) R = \frac{1}{2}(GC + CB - GB) = \frac{1}{2}(k + 2 - 4R - \sqrt{k^2 + (2 - 4R)^2}) , which solves to k = R ( 5 R 2 ) 3 R 1 k = \cfrac{R(5R - 2)}{3R - 1} .

From A G B \triangle AGB , R = 2 A A G B P A G B = A G C B A G + G B + A B = ( 4 R R 2 k ) ( 2 4 R ) ( 4 R R 2 k ) + k 2 + ( 2 4 R ) 2 + 2 R = \cfrac{2A_{\triangle AGB}}{P_{\triangle AGB}} = \cfrac{AG \cdot CB}{AG + GB + AB} = \cfrac{(4\sqrt{R - R^2} - k)(2 - 4R)}{(4\sqrt{R - R^2} - k) + \sqrt{k^2 + (2 - 4R)^2} + 2} .

Substituting k = R ( 5 R 2 ) 3 R 1 k = \cfrac{R(5R - 2)}{3R - 1} into R = ( 4 R R 2 k ) ( 2 4 R ) ( 4 R R 2 k ) + k 2 + ( 2 4 R ) 2 + 2 R = \cfrac{(4\sqrt{R - R^2} - k)(2 - 4R)}{(4\sqrt{R - R^2} - k) + \sqrt{k^2 + (2 - 4R)^2} + 2} and solving numerically gives R 0.2434772 R \approx 0.2434772 , and 1 0 6 R = 243477 \lfloor 10^6 R \rfloor = \boxed{243477} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...